Hubungan Antara Nilai Forced Expiratory Volume In One Second (Fev1) Dengan Kejadian Barrel Chest Pada Penderita Gangguan Paru Obstruksi Di Rumah Sakit Paru Dr. Ario Wirawan Salatiga - , Setianingrum, Isnaini Herawati, S.Fis., M.Sc (2016)
Background: Pulmonary disease much to change the volume spirometry lung examination. In patients with pulmonary disorders, especially obstruction be impaired Forced Expiration Volume in One Second (FEV1) due to the occurrence of lung hyperinflation. Barrel chest is not a disease but a symptom that manifests a disease, generally a sign the final phase due to the addition of COPD lung volume because of constraints which lasted chronic airflow. The Objective of Research: To know the relationship between the value of Forced expiratory Volume In One Second (FEV1) and the incidence barrel chest in Patients with obstructive lung disorder at Pulmonary Hospital Dr. Ario Wirawan, Salatiga. The Benefit of Research: To find out how much significance the relationship between the value of Forced Expiratory Volume in One Second (FEV1) and the incidence barrel chest in patients with obstructive lung disorder at Pulmonary Hospital Dr. Ario Wirawan, Salatiga. The Method of Research: The research in this study was observational with cross sectional study design. Samples were taken with Nonprobably Sampling technique, ie purposive sampling method with inclusion and exclusion criteria. Measurement of FEV1 by spirometry, whereas barrel chest with anthropometry and inspection. Analysis of the data in this study using Spearman (Rho). Result of the Research: Based on the statistical test result count r 0.500, with 0.000 p-value of <0.05 so that Ho refused and Ha accepted. Conclusion: There is a significant relationship between the value of the forced expiration volume in one second (FEV1) and the incidence barrel chest in patients with obstructive pulmonary disorder in the Hospital Dr. Ario Wirawan, Salatiga.